ANALISIS KEMAMPUAN PEMECAHAN MASALAH BENTUK NUMERASI PADA KONTEN MATEMATIKA SMK - Muhamad Yasin; Yuyu Yuhana; Abdul Fatah (LPPM Universitas Bina Bangsa, 2023)
This study aims to analyze students' problem-solving abilities in solving problems on vocational mathematics problems. There are 4 indicators for problem solving abilities, namely identifying data adequacy to solve problems, creating a mathematical model of a problem, choosing and implementing a problem solving strategy, and re-examining the results of the answers that have been made. The research subjects were 30 class XII students of SMK Plus Pakuhaji-Tangerang and the test instruments were math numeration questions at SMK Plus and interview tests. The method used in this research is descriptive qualitative. Based on the research results, it was found that the highest error rate was at the indicator stage for making a mathematical model, namely 50.71% and included in the very high criteria, on other indicators students got quite high criteria. It can be concluded that there are still many students who have difficulty in making mathematical models in the problems presented while in identifying problems the average student is quite able to identify problems but cannot be said to be good or very good because problem solving questions are new things given to students